Kontestasi Abangan-Santri Pasca Orde Baru di Pedesaan Jawa - Yogi Setya Permana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2010)
In 1981 Clifford Geertz delivered the famous typology of Javanese society. He devided Javanese society into three categories; santri, priyayi and abangan. The relations among them are not only in harmonic but also conflictual relations. This article describes the contestation between abangan and santri in Ngandong Village, Gantiwarno District of Klaten. This paper employs Contentious Politics as major theory to describe what were happened in Ngandong Village. The result is that the contestations between them were happened both in formal events and daily life activities.